Annotated Aboriginal Law: The Constitution, Legislation, Treaties and Supreme Court of Canada Case Summaries (2019 ed.) - Imai, Shin (Osgoode Digital Commons, 2018)
Written by Shin Imai, an experienced Aboriginal law practitioner and teacher, this book features the full text of the Indian Act and regulations, accompanied by hundreds of annotations and section-by-section summaries of all significant court decisions interpreting or applying the legislation. As well, this work includes the consolidation of the Indian Act and regulations and hundreds of annotations, the full texts of legislation and regulations including the Indian Oil and Gas Act and the First Nations Land Management Act; a review of the case law under s. 91(24) of the Constitution Act, 1867 [s. 91(24) (division of powers)] and the Canadian Charter of Rights and Freedoms [s. 15 (equality rights), s. 25 (Aboriginal Rights and Freedoms not affected by the Charter) and s. 35(1) (Aboriginal and Treaty rights)]; and a brief annual review of the law, highlights of other legislation related to Aboriginal peoples, important cases, and a summary of the most important Supreme Court of Canada cases on Aboriginal law issues. https://digitalcommons.osgoode.yorku.ca/faculty_books/1377/thumbnail.jpg